2022
DOI: 10.3389/fnins.2022.1026610
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional connectivity in psoriasis patients with depression is associated with their clinical symptoms

Abstract: Psoriasis is a chronic, autoimmune disorder that is related to mental health disorders such as depression. However, few studies have focused on the features of brain activity in psoriasis patients with depression (PPD) and the association between brain activity and disease severity. A total of 29 PPD and 24 healthy controls were involved in this study, and all participants underwent resting-state functional magnetic resonance imaging (fMRI) scanning. The psoriasis area and severity index (PASI) and the self-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
(74 reference statements)
0
2
0
Order By: Relevance
“…47 In another cohort of 29 people with psoriasis and depression and 24 healthy controls, functional magnetic resonance imaging scanning was performed in addition to severity measures of psoriasis (PASI) and a self-assessment of depression (SDS). 48 In comparison to healthy controls, people with psoriasis and depression demonstrated an increased fractional amplitude of low-frequency fluctuation in the left frontal middle brain area (Frontal_Mid_L) and increased functional connectivity between the right hypothalamus region and the right middle cingulum (Cingulum_Mid_R). There was a positive correlation between PASI and SDS in people with psoriasis with depression, while functional connectivity was negatively correlated with SDS and PASI.…”
Section: Symptomsmentioning
confidence: 99%
See 1 more Smart Citation
“…47 In another cohort of 29 people with psoriasis and depression and 24 healthy controls, functional magnetic resonance imaging scanning was performed in addition to severity measures of psoriasis (PASI) and a self-assessment of depression (SDS). 48 In comparison to healthy controls, people with psoriasis and depression demonstrated an increased fractional amplitude of low-frequency fluctuation in the left frontal middle brain area (Frontal_Mid_L) and increased functional connectivity between the right hypothalamus region and the right middle cingulum (Cingulum_Mid_R). There was a positive correlation between PASI and SDS in people with psoriasis with depression, while functional connectivity was negatively correlated with SDS and PASI.…”
Section: Symptomsmentioning
confidence: 99%
“…In an investigation using data from the UK biobank and MRI imaging, it was found that thickness in the right precuneus was increased in people with psoriasis compared to controls only when depression was present 47 . In another cohort of 29 people with psoriasis and depression and 24 healthy controls, functional magnetic resonance imaging scanning was performed in addition to severity measures of psoriasis (PASI) and a self‐assessment of depression (SDS) 48 . In comparison to healthy controls, people with psoriasis and depression demonstrated an increased fractional amplitude of low‐frequency fluctuation in the left frontal middle brain area (Frontal_Mid_L) and increased functional connectivity between the right hypothalamus region and the right middle cingulum (Cingulum_Mid_R).…”
Section: Risk Factors For Psoriasismentioning
confidence: 99%